O PSICÓLOGO NAS POLÍTICAS PÚBLICAS A PARTIR DA CORRELAÇÃO ENTRE A CLÍNICA AMPLIADA E A REDUÇÃO DE DANOS - Rafael Bianchi Silva; Luiza Farias Miani; Graziela Lastória Bonatti (Edufatecie, 2021)
This article aims to go through the concept of expanded clinic and harm reduction in order to add ways of thinking and acting that differ from traditional practices in the psychologist's work context.From this, we will build approximations of these proposals regarding comprehensive health care, thinking about these strategies as ways to allow the guarantee of users' rights and their autonomy / protagonism. We will take as a research strategy a qualitative study, and as a data collection instrument we use Document Analysis, with the aim of describing and representing the content of the documents in a way that guarantees the recovery ofinformation and the possibility of correlations between the contents.It is concluded that, the concept of expanded clinic and harm reduction practices are similar in some aspects, mainly in their conceptions of subject / user As for the work of the psychologist, we understand that both perspectives can potentiate problematizations and extensions of the ways of performance in order to produce more participatory and inclusive actions.